Modeling of cutting process and flow stress under high strain rate - Norfariza, Ab. Wahab (2015)
In the recent past, advances in analytical modeling and finite element methods (FEM) based numerical modeling of metal cutting have resulted in capabilities of predicting the physical phenomena in metal cutting such as forces, temperatures and stresses generated. FEM modeling has emerged as one of the most effective tools that could substitute the conventional time consuming and expensive experimental tests to a great extent. However, accuracy and reliability of these predictions rely on a work material constitutive model describing the flow stress, at which work material starts to plastically deform and the frictional boundary conditions at the tool/chip interface. This work presents an experiment investigation of the overall influence of different cutting condition of orthogonal cutting process on FEM simulation performance to identify and predict the flow stress of workpiece under high strain rate. The overall influence of different cutting condition considers such as different cutting speed, feed rate and rake face angle. The objective of this research works is to model and investigate two critical factors during orthogonal cutting, namely the flow stress characterization of work material and friction characteristics that applicable for FEM simulation. Firstly, an orthogonal cutting test was conducted with variety and large range of cutting condition Then, the same cutting condition was conducted for two-dimensional cutting process of FEM simulation. To identify the flow stress of workpiece under high strain rate for FEM simulation, Johnson-Cook flow stress model had been applied. Johnson-Cook flow stress model had been exploited using commercial available software DEFOR1V1". Johnson-Cook flow stress have five material constants included A, B, C, n and m. The material constants of A, B, and n can be identified using tensile or compress test. While material constants of C and m were identified using inverse calculation by DownHill method. The Johnson-Cook flow stress model had been applied to understand the flow stress of JIS S45C. However, regarding this method only principal force is in good accuracy between experiments and FEM simulation results. The thrust force error result was big which about 40%. Secondly, to-improve the previous proposed method an improvement method to identify flow stress and friction characteristics had also been studied and discussed. Some of the improvement method was identification of repeated time necessary for unsteady state simulation and steady state simulation. Identification of mesh average length, tool radius roundness, tool rake angle and clearance angle were also been studied. Thus, to improve the thrust force result of FEM simulation, friction characteristics had also been identified. Shear friction model had been applied in this study. As a result from this improvement method the thrust force error between experiment and FEM simulation was about 23%. Lower than then previous proposed. method. However, the principal force error between experiment and FEM simulation had getting bigger. Thirdly, a new method to identify friction characteristics during low-speed orthogonal cutting process had been proposed. 'Low-speed orthogonal cutting process was conducted. Then, the same cutting condition of experiment had been applied to two-dimensional cutting process of FEM simulation but with different value of friction characteristics. Identification value of friction characteristics had been conducted. As a result from this method, principal force error was about 8.9% and thrust force error was about 22%. Which both result was better and smaller than previous proposed method. Lastly, a new method to identify flow stress of workpiece and at the same time friction characteristics between tool/chip can be negligible under high strain rate for FEM simulation also been developed and proposed. In this chapter, a new method to identify Johnson-Cook flow stress model by shear-slitting method had been developed. This is because the proposed method can identify flow stress of workpiece under high strain rate and at the same time friction characteristics can be negligible. The result of experiment shows that this method can achieve high strain rate as same as cutting process and the error of flow stress between experiment and FEM simulation is in good accuracy.